A modified projection-iterative method for solution of a singular integral equation with parameters and small nonlinearity - Polishchuk, О. B. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We suggest a modified version of the projection-iterative method of solving a singular integral equation with parameters and small nonlinearity.